Phytoconstituents, Fourier-Transform Infrared Characterization, and Antioxidant Potential of Ethyl Acetate Extract of Corchorus olitorius (Malvaceae) - Dahiru, Mubarak Muhammad; Umar, Abubakar Sadiq; Muhammad, Musa; Waziri, Asma'u Abubakar; Fari, Ibrahim Ishaq; Musa, Zuwaira Yusuf (Sciences of Phytochemistry, 2024)
Oxidative stress is a condition that is characterized by the generation of reactive oxygen species more than the amount endogenous antioxidants can absorb. Several diseases are associated with oxidative stress, notably during disease progression. Thus, the present study aimed to determine the phytoconstituents and antioxidant potential of the ethyl acetate leaf extract of Corchorus olitorius (ELEC). The phytochemicals were qualitatively and quantitatively determined, followed by characterization using Fourier-transform infrared (FTIR) spectroscopy. The antioxidant potential was determined in vitro. Alkaloids, saponins, and flavonoids were detected in concentrations of 8.50 ±2.65, 11.83 ±0.73, and 19.17% ±0.73, respectively. The FTIR spectrum revealed 9 peaks including six at the group frequency region corresponding to alcohols, carboxylic acid, amine salts, alkenes, alkyne, esters, and oxime functional groups. The ELEC exhibited lower total reducing power (11.06 ±1.34 AAE µg/ml) compared to its total antioxidant capacity (49.26 ±2.44 AAE µg/ml) with a higher (60.47% ±2.44) percentage inhibition of peroxidation than AA (37.98% ±1.88). Furthermore, the ELEC exhibited a lower (0.20 ±0.01 nmol/ml) MDA concentration than AA (0.42 ±0.02 nmol/ml). Conclusively, C. olitorius might be applied for the management of oxidative stress-linked ailments and a source of novel therapeutics for these ailments.